Effect of torpor on host transcriptomic responses to a fungal pathogen in hibernating bats - Kenneth A. Field; Brent J. Sewall; Jenni M. Prokkola; Gregory G. Turner; Marianne F. Gagnon; Thomas M. Lilley; J. Paul White; Joseph S. Johnson; Christopher L. Hauer; DeeAnn M. Reeder (Molecular Ecology, 2018)
Hibernation, the use of prolonged torpor to depress metabolism, is employed by mammals to conserve resources during extended periods of extreme temperatures and/or resource limitation. Mammalian hibernators arouse to euthermy periodically during torpor for reasons that are not well understood, and these arousals may facilitate immune processes. To determine whether arousals enable host responses to pathogens, we used dual RNA ‐Seq and a paired sampling approach to examine gene expression in a hibernating bat, the little brown myotis ( Myotis lucifugus ). During torpor, transcript levels differed in only a few genes between uninfected wing tissue and adjacent tissue infected with Pseudogymnoascus destructans , the fungal pathogen that causes white‐nose syndrome. Within 70–80 min after emergence from torpor, large changes in gene expression were observed due to local infection, particularly in genes involved in pro‐inflammatory host responses to fungal pathogens, but also in many genes involved in immune responses and metabolism. These results support the hypothesis that torpor is a period of relative immune dormancy and arousals allow for local immune responses in infected tissues during hibernation. Host–pathogen interactions were also found to regulate gene expression in the pathogen differently depending on the torpor state of the host. Hibernating species must balance the benefits of energy and water conservation achieved during torpor with the costs of decreased immune competence. Interbout arousals allow hibernators to optimize these, and other, trade‐offs during prolonged hibernation by enabling host responses to pathogens within brief, periodic episodes of euthermy.